Design and Synthesis of N-acetylated Gemini Surfactants for Use as Leather Preservatives during the Chrome-tanning Process - Machuca, Laura Marcela; Ojeda, María Florencia Acuña; Gutierrez, Carolina Guadalupe; Murguía, Marcelo César (Current Perspectives on Chemical Sciences Vol. 8, 2021)
A series of N-acetylated non-ionic and cationic gemini surfactants (3a-f) were synthesized and their antifungal potency and surface properties further determined. Critical micelle concentration (CMC), effectiveness of surface tension reduction (gCMC), surface excess concentration (G), and area per molecule at the interface (A) were also determined and the resulting values indicate that the cationic series is characterized by good surface-active and self-aggregation properties. The aim of this work was to compare two novel antifungal agents with 2-(thiocyanomethylthio)-benzothiazole (TCMTB). For this study, two gemini surfactants (3b and 3e) were efficiently prepared and formulated. The antifungal potency of these compounds was tested and their effectiveness as leather preservatives during the chrome-tanning process was assessed using the environmental chamber test (ASTM D 3273-00 Standard) and wet-blue hides on a plate with culture medium (ASTM D 4576-08 Standard). Two strains were used to perform the study: Aspergillus niger ATCC 6275 and Penicillium citrinum ATCC 9849. 3b and 3e showed the ability to preserve hides because of their antifungal activity present in chromium tanning specimens. Compound 3e was found to be a more potent antifungal than compound 3b, but not as potent as TCMTB. This cationic gemini compound (3e) was less toxic than TCMTB for Daphnia magna as a biological model. This work is the result of a patent of invention registered in the patent offices from Argentina.